Hermeneutika Sufistik-Filosofis: Penafsiran Ibn 'Arabi atas Kisah Nabi Musa dan Nabi Khidir dalam QS.Al-Kahfi 60-82. - Muhammad Faizin (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2021)
This article examines the story of the Prophet Musa and the Prophet Khidir which are contained in Qs. Al-Kahfi 60-82. It is commonly known that the story tells of the mystical and suprarational events experienced by Prophet Musa while studying from Prophet Khidir. However, in this article, the study of the story of the Prophet Musa and Khidir becomes more interesting because - by using a descriptive-analytical approach - the writer tries to uncover the story through Ibn 'Arabi's perspective as stated in his commentary; Tafsi>r Ibn 'Arabi. As we know that the interpretation of Ibn 'Arabi by Husain al-Zahabi is categorized as a Sufi nadzari interpretation, which is an interpretation that is built to strengthen and promote philosophical and mystical theories adhered to by the commentators. As a result, Ibn 'Arabi's interpretation of the story is very different from the existing mainstream interpretation. In that sense, Ibn 'Arabi brought his interpretation of the story into the Sufistic-philosophical discourse. Because, in this story Ibn 'Arabi does not interpret it as a human journey physically (wadak) but is interpreted symbolically-allegorically, namely a spiritual journey, in which case the Prophet Musa is interpreted as a heart that wants to reach maqa> m kamal or makrifat to Allah through the guidance of the Prophet Khidir which is interpreted as a holy reason (al-'aql al-qudsi>).